Adaptability and Life Satisfaction: The Moderating Role of Social Support - Zhou, Mi; Lin, Weipeng (Frontiers in Psychology, 2016)
The purpose of this study was to investigate the moderating role of social support in the relationship between adaptability and life satisfaction. Data were collected from 99 undergraduate freshmen in a Chinese university using a lagged design with a one-month interval. Results demonstrated that social support moderated the relation between adaptability and life satisfaction, such that the positive relation between adaptability and life satisfaction was stronger for individuals with higher levels of social support than for individuals with lower levels of social support. The theoretical and practical implications of this result are discussed.